2018
DOI: 10.1007/s00192-018-3753-9
|View full text |Cite
|
Sign up to set email alerts
|

Obstetric anal sphincter injury: a systematic review of information available on the internet

Abstract: Online information concerning obstetric anal sphincter injury often uses language that is inappropriate for a lay audience and lacks sufficient accuracy, credibility, and reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 27 publications
3
24
0
Order By: Relevance
“…Few websites provided a complete description of the management options (ie, radiological surveillance vs surgical treatment). Similar limitations have been described for other health conditions such as pancreatic cancer and gynecological disorders [4,5,7,35,36]. Despite the overall lack of high-quality web-based health information, a few sources were excellent.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…Few websites provided a complete description of the management options (ie, radiological surveillance vs surgical treatment). Similar limitations have been described for other health conditions such as pancreatic cancer and gynecological disorders [4,5,7,35,36]. Despite the overall lack of high-quality web-based health information, a few sources were excellent.…”
Section: Discussionmentioning
confidence: 72%
“…Across different health conditions, these high-quality websites represent the minority of cases. Three studies comparing the educational materials for obstetric and pelvic diseases reported that only 5% (3/58) [5], 15% (8/54) [7], and 4% (1/24) [4] of the materials achieved DISCERN scores greater than 60. Encouragingly, in our review, high-quality websites appeared as earlier search hits (our 2 high scorers appeared as the 16th and 17th hits), suggesting that they are more recognizable sources of information for internet users.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dissemination of inaccurate health information has been clearly demonstrated in other areas of women's health. [7][8][9] The implications and sequelae of this information is difficult to quantify.…”
Section: Relevancementioning
confidence: 99%
“…[6] Previous systematic reviews of online information in areas of women's health including: endometriosis; obstetric anal sphincter injury; and bladder pain syndrome have revealed poor quality, accuracy, and readability. [7][8][9] A single systematic review relating to online information of fibroids has been published, however this only assess quality. [10] We systematically assessed the accuracy, quality, and readability of webpages providing information regarding the diagnosis and management of fibroids.…”
Section: Introductionmentioning
confidence: 99%